The Bremen-Cog: reconstructed one more time - Tanner, Pat; Belasus, Mike (Archaeonautica, 2022)
Within the three-year project “Between the North Sea to the Norwegian Sea: interdisciplinary research on the Hanse” (2015-2018), established by the Leibniz Association at the German Maritime Museum, questions were raised on the seaworthiness of ships of the Bremen-type1. The main object of the resulting research was the late medieval Bremen-Cog, from 1378-1379, which was found in 1962 in the River Weser close to Bremen and is today on display at the museum in Bremerhaven.The project did not begin with the intention of reconstructing an already reconstructed ship find, but rather to examine the overall hydrodynamic and seakeeping abilities of the ship, in order to see whether ships of this building method were the oceangoing trading vessels of their era, and could sail the North Atlantic all the way to Iceland.In order to evaluate the complex concepts of seakeeping and oceangoing, a reliable hull form as well as accurate construction details are required. Establishing the vessel’s overall hydrostatic characteristics, static and dynamic stability, and overall sailing abilities, requires detailed calculations using the centres of buoyancy, flotation and gravity. Dans le cadre du projet triennal « Entre la mer du Nord et la mer de Norvège : recherche interdisciplinaire sur la Hanse » (2015-2018), mis en place par l’Association Leibniz au Musée maritime allemand, des questions ont été soulevées sur la navigabilité des cogues du type de celle de Brême. Notre attention s’est donc portée sur la cogue de Brême, datée de la fin du Moyen Âge, précisément de 1378 ou 1379, et trouvée en 1962 dans la Weser près de Brême et qui est aujourd’hui exposée au musée de Bremerhaven.Le projet n’a pas commencé avec l’intention de proposer une nouvelle hypothèse de restitution d’un navire par ailleurs déjà restitué, mais plutôt d’examiner les caractéristiques hydrodynamiques et de tenue à la mer du navire. Ceci afin de voir si les navires de ce type ont pu participer à un commerce océanique en navigant sur l’Atlantique Nord jusqu’à ...